Theranostics in breast cancer - Vorster, M.; Hadebe, B. P.; Sathekge, M. M. (Frontiers in Nuclear Medicine, 2023)
Breast cancer is a complex disease which cons.tutes the leading cause of cancer in women globally. Conven.onal treatment modali.es include surgery, chemotherapy, radia.on therapy, and hormonal therapy; all of which have their limita.ons and oBen result in significant side effects or toxicity. Targeted radionuclide therapy based on a theranos.c approach, has been successfully applied in several malignancies, such as prostate cancer, thyroid cancer, and neuro-endocrine tumours. Several studies have highlighted the poten.al of theranos.c applica.ons also in breast cancer.This review aims to provide an overview of the most promising current-and future theranos.c approaches in breast cancer.The discussion includes pre-clinical as well as clinical data on some of the most successful targets used to date. Examples of poten.al theranos.c approaches include those targe.ng the HER-2 expression, angiogenesis, aspects of the tumour microenvironment, GRPr-, PSMAand CXCR-4 expression. Several challenges to widespread clinical implementa.on remain, which include regulatory approval, access to the various radiopharmaceu.cals and imaging technology, cost-effec.veness, and the absence of robust clinical data.Theranos.c approaches have the poten.al to greatly improve diagnosis, treatment, and outcomes for pa.ents with breast cancer. More research is needed to fully explore the poten.al of such approaches and to iden.fy the best poten.al targets, considering feasibility, costs, efficacy, side effects and outcomes.